Regulation of the glutamate-glutamine transport system by intracellular pH in Streptococcus lactis. - Poolman, B (1987)
Various methods of manipulation of the intracellular pH in Streptococcus lactis result in a unique relationship between the rate of glutamate and glutamine transport and the cytoplasmic pH. The initial rate of glutamate uptake by S. lactis cells increases more than 30-fold when the intracellular pH is raised from 6.0 to 7.4. A further increase of the cytoplasmic pH to 8.0 was without effect on transport. The different levels of inhibition of glutamate and glutamine transport at various external pH values by uncouplers and ionophores, which dissipate the proton motive force, can be explained by the effects exerted on the intracellular pH. The dependence of glutamate transport on the accumulation of potassium ions in potassium-filled and -depleted cells is caused by the regulation of intracellular pH by potassium movement.